Pengaruh Receivable Turnover dan Working Capital Turnover terhadap Profitability pada Perusahaan Farmasi yang Terdaftar di BEI Periode 2014-2018 - Salma Maisa; Fifi Afiyanti Tripuspitorini; Armansyah M. Sarusu (Indonesian Journal of Economics and Management, 2020)
This final project research is aimed to determine the effect of RTO and WCTO on ROA on pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) period 2014-2018 period. The techniques are used in this research is Purposive Sampling and obtained 7 Pharmaceutical Companies on the IDX which were used as research samples. Secondary data are used in the form of company annual financial statements. The research method used are descriptive and quantitative research. The test is done by panel data regression method which is processed using eviews 10. The selected panel data regression method is the Fixed Effect Model. The results showed that simultaneously RTO and WCTO had a significant effect on profitability (ROA) of pharmaceutical companies listed on the IDX. The partial results showed that RTO had a significant negative effect on profitability (ROA) while WCTO had no significant effect on profitability (ROA) for pharmaceutical companies listed on the IDX.